PENGARUH UKURAN PERUSAHAAN, TANGIBILITY, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Daniel Pramana Surbakti; Robinhot Gultom; Saur Melianna (STKIP Subang, 2026)
This study aims to examine and analyze the effect of company size proxied by natural logarithm of total assets (LNTA), Tangibility proxied by the fixed assets ratio (FAR), and liquidity proxied by the current ratio (CR) on company value proxied by the price to book value ratio (PBV) in property and real estate companies listed on the Indonesia Stock Exchange (IDX). The population in this study consisted of 92 companies, with a sample of 61 companies selected using purposive sampling. The data analysis method used was multiple linear regression analysis. The results show that partially, the variables of company size,tangibility, and liquidity have a positive and significant effet on company value. Simultaneously, these three independent variables also have a positive and significant effect on company value. The coefficient of determination test results show that LNTA, FAR, and CR are able to explain 99.3% of the variation in company value, while the remaining 0,7% is infuluenced by other variables outside the research model.